23rd International Conference on Offshore Mechanics and Arctic Engineering, Volume 1, Parts a and B 2004
DOI: 10.1115/omae2004-51629
|View full text |Cite
|
Sign up to set email alerts
|

Full Scale Data Comparison for the Horn Mountain Spar

Abstract: The Horn Mountain Production Spar was installed in 5,400 feet of water in June 2002. This was the deepest floating production unit at that time. A comprehensive instrumentation program was initiated to measure spar and riser responses (Edwards et al, DOT 2003). The present paper discusses the results of these measurements and comparison with analytical predictions of spar behavior during two selected events, hurricane Isidore in September 2002 and a summer storm in August 2003. Particular attention has been pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The findings seem to confirm both the robustness of the current spar design practice and the accuracy of the spar analysis tools. Halkyard et al (2004) and Tahar et al (2005) have compared measured spar responses such as motion and mooring line tensions with numerical predictions. In Halkyard et al (2006), the work was extended based on comparison of the full scale data during hurricane Isidore.…”
Section: Hurricanes and Other Extreme Environmental Eventsmentioning
confidence: 99%
“…The findings seem to confirm both the robustness of the current spar design practice and the accuracy of the spar analysis tools. Halkyard et al (2004) and Tahar et al (2005) have compared measured spar responses such as motion and mooring line tensions with numerical predictions. In Halkyard et al (2006), the work was extended based on comparison of the full scale data during hurricane Isidore.…”
Section: Hurricanes and Other Extreme Environmental Eventsmentioning
confidence: 99%
“…The reason why Horn Mountain Spar was selected as the accuracy test model is because of its actual field measurement data of dynamic responses under Hurricane Isidore in September 2002, and since then many researchers used this data to validate their time-domain simulations (Halkyard et al [6]; Tahar et al [11]; Theckumpurath et al [7]). The irregular wave condition under Hurricane Isidore is represented by JONSWAP spectrum with 6.3m of significant wave height and 12.2sec of spectral peak period.…”
Section: Validation Of the Time-domain Analysismentioning
confidence: 99%
“…For example, Ormberg and Larsen [1] compared the results from coupled and uncoupled analyses in the time-domain which showed a tendency of underestimation of design parameters such as platform displacements and the line tensions when using uncoupled methods. Halkyard et al [6] and Theckumpurath et al [7] solved the dynamic responses of Horn Mountain Spar subjected to Hurricane Isidore, and compared the results with the full scale measurement data. Wichers and Devlin [4] also conducted a fully-coupled time-domain analysis for dynamics of a turret-moored FPSO, which concluded that coupling effects is important especially when there exists a loop-current.…”
Section: Introductionmentioning
confidence: 99%
“…Floating structures of deep-water platforms, such as tension leg platform (TLPs), 9 SPARs, [10][11][12] semi-submersible platform (SEMIs), 13 and FPSOs, [14][15][16][17][18] have been successfully and widely applied, whereas the monitoring of SYMs in shallow water has seldom been reported. In this study, the method of monitoring SYM in Bohai Bay was carried out.…”
Section: Introductionmentioning
confidence: 99%